Multiscale modeling of plasmonic enhanced energy transfer and cavitation around laser-excited nanoparticles. Issue 9 (9th February 2017) - Dagallier, Adrien; Boulais, Etienne; Boutopoulos, Christos; Lachaine, Rémi; Meunier, Michel
Abstract : Multiscale modeling and measurement of the ultrafast laser excitation of plasmonic nanostructures and their subsequent nanosecond bubble dynamics. Abstract : Nanoscale bubbles generated around laser-excited metallic nanoparticles are promising candidates for targeted drug and gene delivery in living cells. The development of new nanomaterials for efficient nanobubble-based therapy is however limited by the lack of reliable computational approaches for the prediction of their size and dynamics, due to the wide range of time and space scales involved. In this work, we present a multiscale modeling framework that segregates the various channels of plasmon de-excitation and energy transfer to describe the generation and dynamics of plasmonic nanobubbles. Detailed comparison with time-resolved shadowgraph imaging and spectroscopy data demonstrates that the bubble size, dynamics, and formation threshold can be quantitatively predicted for various types of nanostructures and irradiation parameters, with an error smaller than the experimental uncertainty. Our model in addition provides crucial physical insights into non-linear interactions in the near-field that should guide the experimental design of nanoplasmonic materials for nanobubble-based applications in nanomedicine.